ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPATUHAN WAJIB PAJAK MEMBAYAR PAJAK HOTEL, PAJAK RESTORAN DAN PAJAK HIBURAN DI KOTA DENPASAR - Trisnawati, Ni Luh Mika; Sudirman, I Wayan (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME 04.NO.12.TAHUN 2015, 2016)
Local taxes still play one’s role, in order to increase tax revenues in the city of Denpasar. Under Law Number 28 of 2011, the tax collection of hotels, restaurants and entertainmentsshall apply self assessment system, so that the taxpayers awareness is the most crucial factor ofthe taxpayersobedience in implementing their obligations and rights in the field of taxation.This study aimstoanalyzethe effect factors  of the taxpayerson their obedienceto pay thehotel, restaurant andentertainmenttaxesin Denpasar. The method used was quantitative research method. The source of data used primary data. Data collection methods used were questionnaires, observation and interviews. Respondents were determined by the formula of slovin, totaling 154 taxpayers comprised of 56 hotel taxpayers, 77 restaurant taxpayers, and 21 entertainment taxpayers. Sampling was done by accidental sampling.Results of hypothesis testing conducted by path analysis showed that,1) the tax knowledge, quality of service and tax audits positivelyinfluenced on the awareness of the taxpayers to pay the hotel, restaurant and entertainment taxes in Denpasar; 2) the knowledge of tax, service quality, tax audits and taxpayer awareness  positivelyaffected on the taxpayersobedience to pay the hotel, restaurantand entertainment taxes in Denpasar; 3) the knowledge of tax does not significat effect on the taxpayersobedience through awareness of the taxpayers to pay the hotel, restaurant and entertainment taxesin the City of Denpasar.Service quality, and tax audits indirectlygave significat effect on the taxpayersobedience through awareness of the taxpayers to pay the hotel, restaurant and entertainment taxesin the City of Denpasar.The awareness of taxpayers mediatedfully the tax knowledge, quality of service, and tax audits on the taxpayersobedience. Based on the results of hypothesis testing that therewere some implications of the knowledge of the public about the importance of paying taxes, through the continuous dissemination of various policies associated with the hotel, restaurant and entertainment taxes in Denpasar so that people are aware and obedient with paying taxes.
Keywords: obedience, tax knowledge, quality of service, tax audits